CLINICAL EFFECTIVENESS OF DIFFERENT METHODS HERNIOPLASTY OF INGUINAL HERNIAS - Huseynova, G.T.; Джамалов Ф. Г.; Ахундов І. Т.; Гусейнов Ш. Г. (World of Medicine and Biology, 2015)
Abdominal hernias occur at any age, both men and women in approximately,- 2-4% of the total population, accounting for from 8 to 24% of all surgical patients contingent. In the structure of the surgical operation-herniotomy ranks third place after appendectomy and cholecystectomy. Recurrence of hernia violate labor activity of patients, performing physical work, brings moral suffering, undermines confidence in the surgical treatment, returns strangulation risk of internal organs. Currently described more than 300 methods of herniotomy, which is based on the principle of strengthening the back (Bassini, Marcy) or the front (Gerard, Spasokukotsky) wall of the inguinal canal. Modern methods of plastics by Shouldice, Mc Vay, Halstead, Postempsky, is essentially a modification of the method by Bassini, lead to tension tissues during convergence aponevrosis. This is probably, one of the principal reasons for recurrence of hernias. Later the above methods have begun to develop nontension methods plastic repair of inguinal canal, also methods using foreign materials Surgeons attempts use at herniotomy synthetic materials initially aimed at increasing the reliability plastic repair of inguinal canal. In the seventies developed a method not stretch plastic back wall of the inguinal canal with the help of polyester mesh. Polymer mesh is fixed to inguinal ligament and aponeurosis of the transversus abdominis below spermatic cord, to strengthen the back wall after separation, sewing and cutting off the hernial sac. Mesh graft is attached to the pubic tubercle region, is formed on top of the mesh deep ring around the spermatic cord. Apone urosis of the external oblique abdominal muscle sutured over the spermatic cord. Over 10-14 days mesh grows its own connective tissue and forms a new bottom of the inguinal canal. Thanks to decline the fixing edges fascia and muscles to the inguinal ligament turns out the so-called "free from tension" - non tension alloplasty. Nevertheless, to the nineties of the 20 th century when alloplasty inguinal hernias are widely engaged in only a few European and American clinics. Only in 1989 after the publication by Lichtenstein I.L. of his method hernioplasty "tension free" using polypropylene implants begins its widespread introduction. Author on the large amount of material demonstrates excellent result - 0,2% recurrence with minimal wound complications. All recurrences were studied, their reason were technical defects made in the period of developement of the methodology. As hernia repair is the third frequency intervention, material costs for the operation should be minimal, and the recovery of physical activity and a return to professional activates as much as possible fast. All of these requirements with inguinal hernias, in our opinion, corresponds hernioalloplasty using the Trabucco method. I.V. Sukhinina (2010) based on the experience of treatment of 146 patient also believes that the seamless plastic inguinal canal by the Trabucco method can be successfully used in patient with all forms of inguinal hernias and the time of recovery, rehabilitation and relapse rates in lond-term period is sugnificantly less than for hernia repair by I.L.Lichtenstein. In conclusion , it should be noted that the analysis of the literature on surgical treatment of patient with inguinal hernias, revealed that this problem is still important in modern abdominal surgery. This is due, on the one side, the steady increase in the number of patients with this disease, on the other still remain dissapointing results of surgical treatment. Despite the variety of proposed methods plastics of inguinal hernia by local tissues, the recurrence rate is 6-35%. High rate of relapse after conventional types of plastics inguinal hernia helped develop mesh implants which have been widely used for the treatment of postoperative and recurrent ventral hernias. Despite the many proposed materials for alloplasty the issue about technique, and optimal material for hernioplasty remains unresolved.
Keywords: inguinal hernia; plasty of the inguinal canal; method Trabucco; hernioalloplasty by I. L. Lichtenstein